Between efficiency and comfort: the organization of domestic work and space from home economics to scientific management, 1841–1913. (2nd January 2019) - Paris, Ivan
ABSTRACT: The impact of Frederick Taylor's theories upon household management was dramatic. Terms such as efficiency and scientific management had already become commonplace amongst US home economists during the first decade of the twentieth century, but precisely the fact that these principles were applied so quickly to the complex working environment of the home shows that it was an environment which was ready to receive such ideas. This article seeks to show how the domestic context had already undergone profound change in that direction in the second half of the 1800s, primarily thanks to the work of Home Economics theorists such as Catharine Beecher. Her approach was characterized by an efficiency-oriented push, which aimed to save labor and space by reorganizing both. These changes also involved the concept of comfort and the structure of the American middle-class home, thus preparing the ground for many of the changes which became fully consolidated during the 1900s.